LEGITIMASI KEKUASAAN ELIT AGAMA DI KEDIRI - Khaerul Umam (Religi: Jurnal Studi Agama-agama, 2017)
The role of religious elites (read: religious leaders) in the City of Kediri cannot be separated from its influence as a bearer of religious teachings. Religion as an institution that teaches values requires humans to bring it so that it can be conveyed to all humans. The role of religious leaders is dialectical with the needs of society. Although on the one hand he teaches religion, which has strict rules and restrictions, but in practice, these elites must be able to read the socio-cultural dynamics that exist in society, so that religion and society can go hand in hand without having to negate one another. On the other hand, the community is either voluntary or forced to recognize the power possessed by religious elites, in addition to fulfilling spiritual needs that can only be obtained from the elites, as well as an effort to maintain the values agreed upon by the community.